How to Prevent and Mitigate Hypersensitivity Reactions to Biologicals Induced by Anti-Drug Antibodies? - Vultaggio, Alessandra; Perlato, Margherita; Nencini, Francesca; Vivarelli, Emanuele; Maggi, Enrico; Matucci, Andrea (Frontiers in Immunology, 2021)
Biologicals are widely used therapeutic agents for rheumatologic diseases, cancers, and other chronic inflammatory diseases. They are characterized by complex structures and content of variable amounts of foreign regions, that may lead to anti-drug antibodies (ADA) development. ADA onset may limit the clinical usage of biologicals because may decrease their safety, in fact they are mainly associated with immediate hypersensitivity reactions (HSRs). Development of ADA is reduced by concomitant immunosuppressive treatment, while it is increased by longer intervals between drug administrations, thus regular infusion regimens should be preferred to reduce HSRs. Once ADA have formed some procedures can be implemented to reduce the risk of HSRs. ADA may belong to different isotype; the detection of IgE ADA is advisable to be assessed when high and early ADAs are detected, in order to reduce the risk of severe HRs. In patients who need to reintroduce the culprit biological, as alternative therapy are not available, drug desensitization (DD) may be applied. Desensitization shoud be conceptually dedicated to patients in which an IgE-mediated HSR, however it can be performed also in patients who had developed non IgE-mediated HSRs. Although the underlying mechanisms behind successful DD has not been fully clarified, the DD procedure is associated with the inhibition of mast cells degranulation and cytokine production. Additionally, some data are emerging about the inhibition of drug-specific immune responses during DD.